Sustainable Energy Market Transformation at the Intersection of Human Evolution, Digital Technology, and Economics - Rajagopala Bale, Shridevi (Digital Repository of Theses - SSBM Geneva, 2024)
Our climate is changing due to increase in temperature which is directly linked to the carbon emitted by our industries, transportation, and modern lives. Primarily this carbon is emitted due to burning of fossil fuels (a major source of Energy) which is considered as dirty fuel. To address the growing demand for energy and reduction of carbon emissions energy market need to undergo transformation. While there are multiple greener technologies which can bring down the carbon emissions but there is no research done on what kind of transformations energy market has to undergo at the intersection of economics and digital technologies. This research aims to address this gap. The methodology adopted can be divided into two parts. a) Research on how to reduce the energy demand and decouple the economic growth with energy. b) Study different green technologies and abatement technologies available for Energy companies to adopt. The research showed different energy sources like Solar Power, Wind Energy, Nuclear Energy, Battery Technology, Biofuels, Geothermal and Hydrogen which will help reduce the emissions. To enable consumption of these form of energies the Energy Market transformations needs to happen. Transmission and Distribution network needs to be modernized and expanded to meet the demands. Carbon Capture technologies needs to be adapted along with transportation and storage which is giving rise to new financial markets with carbon as commodity. This helps ensure the balance of emissions and absorption of carbon. Battery Manufacturing needs to be scaled up to meet the huge load of storage of renewable energy. Electric Vehicle (EV) Charging infrastructure needs to be scaled at a very rapid pace to increase the uptake of electricity for mobility and reduce range anxiety. Having said this the mobility sector also needs to undergo transformation to bring down the cost of the EV vehicles and make it ubiquitous. The sector has to scale Hydrogen powered vehicles to solve the requirements of high power for heavy loads transportation. For customers who are not willing or cannot move to EV or Hydrogen powered vehicles, solutions like Biofuel, Sustainable Aviation Fuels must be provided. There is a need to increase blending plants for Biofuels and Sustainable Aviation fuel and supply greener fuel in the same supply chain network, without modifying the automotive involved. Enabling this is digital technologies which play crucial role in connecting stakeholders across ecosystem, brining insights into operations and recommend actionsFurther research on how to fund this change and the ecosystem to enable this transformation are required.